2018
DOI: 10.1080/15504263.2018.1498565
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in Treatment-Seeking Substance-Dependent Populations: Validation of the Social and Emotional Loneliness Scale for Adults–Short Version

Abstract: Objectives: Objectives: Loneliness is a distressing emotional experience that is likely to be prevalent among people accessing treatment for substance dependence problems. The first aim of the current study was to report on the validity of the Social and Emotional Loneliness Scale for Adults-Short Version (SELSA-S), a multidimensional measure of loneliness, for use in substance-dependent treatment populations. In order to further the understanding of loneliness among this population, loneliness was examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The SELSA-S has been used among samples with serious mental illness (Sheridan et al, 2015) and substance dependence (Ingram et al, 2018), all characteristics which are prevalent among people experiencing homelessness (Teesson et al, 2000(Teesson et al, , 2004. As such, the SELSA-S was chosen as being the most appropriate loneliness scale for people experiencing homelessness because it is briefer, multifactorial and more suitable for people with cognitive impairment.…”
Section: The Selsa-s Scalementioning
confidence: 99%
“…The SELSA-S has been used among samples with serious mental illness (Sheridan et al, 2015) and substance dependence (Ingram et al, 2018), all characteristics which are prevalent among people experiencing homelessness (Teesson et al, 2000(Teesson et al, , 2004. As such, the SELSA-S was chosen as being the most appropriate loneliness scale for people experiencing homelessness because it is briefer, multifactorial and more suitable for people with cognitive impairment.…”
Section: The Selsa-s Scalementioning
confidence: 99%
“…All people trying to treat the addiction face a sense of loneliness. This painful emotional experience is exhibited with more severity in addicted individuals compared to the general population; they are weaker in terms of physical and mental health that is associated with this level of loneliness (12). Sense of loneliness can lead to depression (13), which is considered a major predictor variable for highrisk behaviors (14).…”
Section: Introductionmentioning
confidence: 99%
“…Future research in this area should consider inclusion of a control condition and use of experimental methodology to ensure that any changes examined are not attributable to treatment as usual. While one study has found that those who had recently entered into residential treatment were lonelier than participants who had resided there longer [7], another study suggests that residing in a therapeutic community treatment setting might contribute to feelings of loneliness and social distancing [48]. Future researchers should consider the timing of providing loneliness interventions for this population (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is also accumulating evidence to link loneliness to poorer mental health [4] and increased alcohol misuse and drug use [5,6]. A recent study found that people who report problems with substance use are seven times more likely to experience frequent loneliness than the general population [7]. In addition, this study found that people with substance use disorders (SUD) are five times more likely to deem loneliness as a concern when compared with the general population [7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation